Homologous recombination in the nuclear genome of Chlamydomonas reinhardtii. - Sodeinde, O A (1993)
Nuclear transformation of the unicellular green alga Chlamydomonas reinhardtii has thus far been characterized by integration of the introduced DNA into nonhomologous sites. In this study, the occurrence of homologous recombination events during transformation was investigated with the intent of developing strategies for gene targeting and gene disruption. Homologous recombination was monitored by using nonfunctional 5' and 3' deletion derivatives of the wild-type C. reinhardtii nit1 gene (encodes nitrate reductase) as selectable markers (p5' delta and p3' delta respectively) and the low reverting nit1-305 strain as the transformation recipient. After introduction of the DNA into the cell, intermolecular recombination between p5' delta and p3' delta occurs at a high frequency to restore a functional nit1 gene, indicating the presence of homologous recombination machinery in mitotic cells. Gene-targeting events at the nit1 locus were selected by restoring nit1-305 cells to prototrophy after transformation with only p5' delta and were confirmed by analysis of genomic DNA. By comparing the number of transformants obtained after transformation with p5' delta to the number obtained after transformation with a functional nit1 gene, the frequency of homologous-to-random integration events ranged between 1:1000 after glass bead-mediated transformation and 1:24 after bombardment with DNA-coated tungsten microprojectiles.